A New Reference Material for Tritium Organic Molecules in Sediment: Results of an International Intercomparison Exercise. Issue 2 (6th April 2018) - Warwick, Phillip E.; Croudace, Ian W.; Marsh, Richard M.; Baglan, Nicolas; Kim, Sang Bog
Abstract : Solid matrix 3 H reference materials are challenging to prepare given the volatile nature of 3 H and are often unrepresentative of the range of 3 H forms that may be encountered during routine analysis. As a result, few 3 H reference materials are currently available, undermining verification of analytical techniques for environmental 3 H measurement. To address this, an International Working Group on Organically‐Bound Tritium Analysis determined to produce a tritium natural matrix reference material (NMRM). The reference material comprises marine sediment blended with sewage sludge contaminated with 3 H‐organic species arising from authorised discharges from a radiopharmaceutical manufacturing site. Previous studies have demonstrated that the 3 H species have persisted in the environment over three decades providing valuable supporting data to underpin the characterisation of the NMRM. The preparation and characterisation of the NMRM are described along with the subsequent application of the reference material in an international intercomparison exercise involving nineteen laboratories from nine countries. A reference value of 168 ± 22 Bq kg −1 was derived from the data arising from the proficiency test. Key Points: A new tritiated organic molecule in sediment natural matrix reference material has been prepared. The RM incorporates a range of tritiated organic molecules demonstrated to be stable over considerable time periods. Characterised by an international proficiency test involving 19 laboratories, deriving a reference value of 168 ± 22 Bq kg −1 .